ANTESEDEN KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL DAN MENENGAH (Aplikasi PP No 23 Tahun 2018) - Arief Permana Putra; Yoseph Agus BBN (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
The Indonesian government changes the tax rate for businesses that generate certain income in 2018. This study aims to examine the effect of changes in tax rates, knowledge of tax regulations, and the services quality of the tax officers against taxpayers compliance in the MSME sector in Tangerang Regency with application of PP no 23/2018. This research is a quantitative descriptive study. The population in this study was 1,851 people. The type of data used in this study, namely primary data, data collection methods used in this study in the form of a questionnaire. The sample selection technique used in this study is convenience sampling. The number of samples used in this study were 115 people. The software used in this study is SPSS 24.0 Software. This study concludes of changes in tax rates, knowledge of tax regulations, and the services quality of the tax officers have a positive effect on taxpayer compliance for MSME entrepreneurs in Tangerang Regency.